PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON HIDUP BERSAMA ALAM UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS III SD NEGERI TEGALREJO II YOGYAKARTA - Apriliya Findy Yonanta; Arip Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop Powtoon-based animated video learning media on the topic Living Together with Nature to improve the learning outcomes of third-grade students at SD Negeri Tegalrejo II Yogyakarta. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were third-grade students, and data were collected through interviews, observations, questionnaires, and learning outcome tests. The feasibility of the media was validated by media and material experts, while its practicality and effectiveness were analyzed using teacher and student response questionnaires as well as pretest and posttest results. The findings indicate that the Powtoon-based animated video learning media is highly feasible, with an average validation score of 3.9 from media experts and 3.7 from material experts. Teacher and student responses were categorized as very good, with average scores of 3.5 and 3.75, respectively. Student learning outcomes showed a significant improvement, as the average pretest score of 43 increased to 81.6 in the posttest. The results of the Paired Sample T-Test showed a significance value of 0.000 (< 0.05), indicating a significant difference in learning outcomes before and after the use of the media. Therefore, Powtoon-based animated video learning media is effective in improving IPAS learning outcomes for third-grade elementary school students. Keywords: Learning media, Powtoon, IPAS, Learning Outcomes